From Micropores to Ultra-micropores inside Hard Carbon: Toward Enhanced Capacity in Room-/Low-Temperature Sodium-Ion Storage - Yang, Jinlin; Wang, Xiaowei; Dai, Wenrui; Lian, Xu; Cui, Xinhang; Zhang, Weichao; Zhang, Kexin; Lin, Ming; Zou, Ruqiang; Loh, Kian Ping; Yang, Quan-Hong; Chen, Wei (Nano-micro letters, 2021)
Highlights Hard-carbon anode dominated with ultra-micropores (< 0.5 nm) was synthesized for sodium-ion batteries via a molten diffusion–carbonization method. The ultra-micropores dominated carbon anode displays an enhanced capacity, which originates from the extra sodium-ion storage sites of the designed ultra-micropores. The thick electrode (~ 19 mg cm −2 ) with a high areal capacity of 6.14 mAh cm −2 displays an ultrahigh cycling stability and an outstanding low-temperature performance. Pore structure of hard carbon has a fundamental influence on the electrochemical properties in sodium-ion batteries (SIBs). Ultra-micropores (< 0.5 nm) of hard carbon can function as ionic sieves to reduce the diffusion of slovated Na + but allow the entrance of naked Na + into the pores, which can reduce the interficial contact between the electrolyte and the inner pores without sacrificing the fast diffusion kinetics. Herein, a molten diffusion–carbonization method is proposed to transform the micropores (> 1 nm) inside carbon into ultra-micropores (< 0.5 nm). Consequently, the designed carbon anode displays an enhanced capacity of 346 mAh g −1 at 30 mA g −1 with a high ICE value of ~ 80.6% and most of the capacity (~ 90%) is below 1 V. Moreover, the high-loading electrode (~ 19 mg cm −2 ) exhibits a good temperature endurance with a high areal capacity of 6.14 mAh cm −2 at 25 °C and 5.32 mAh cm −2 at − 20 °C. Based on the in situ X-ray diffraction and ex situ solid-state nuclear magnetic resonance results, the designed ultra-micropores provide the extra Na + storage sites, which mainly contributes to the enhanced capacity. This proposed strategy shows a good potential for the development of high-performance SIBs.